Development and evaluation of an external second victim support program for nurses: a single-group feasibility study - Eun Young Choi; Jeehee Pyo; Minsu Ock; Haeyoung Lee (BMC, 2024)
Abstract Background Psychological support programs can help nurses who involved in patient safety incidents. However, most of these programs are operated internally by healthcare providers and utilize peer supporters, which may take a long time to implement. Therefore, there is a need to develop programs that can be used by healthcare providers in healthcare institutions that have difficulty implementing their own programs. This feasibility study aimed to develop an external support program for nurses as second victims and to examine the feasibility, acceptability, and impact of the program. Methods This study was conducted using a single-group pretest-posttest design. Nurses who experienced patient safety incidents were recruited through posters at three advanced general hospitals, as well as open online recruitment and via a research agency panel from September 2020 to April 2021. The 11 participants attended a total of three one-on-one counseling sessions. Feasibility was evaluated based on participant recruitment and retention, resource availability, program procedures, and the practicability of data collection. Acceptability was assessed through program satisfaction and participant feedback. Psychological impact was measured using the Impact of Event Scale-Revised Korean version. Results Out of 26 applicants, 11 (42.3%) completed the program, with 10 (38.5%) participants completing both pre and post-program surveys. Most participants responded that they were satisfied with the program and expressed their intention to recommend the program to others and participate in it again if similar situations arise. The participants' median total IES-R-K score decreased significantly from 30.0 to 16.0 (p = 0.028, r = 0.67). Conclusion This study demonstrates the feasibility of an external second victim support program and provides preliminary data suggesting its potential to alleviate the psychological impact of participants. To overcome the limitations of this study, it is necessary to conduct additional controlled trials with a longer follow-up period and a larger sample size.